Republic of Tajikistan : Staff-Monitored Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The proposed Staff-Monitored Program (SMP) in Tajikistan includes a balanced budget objective with a view to securing the inflation goal. While public financial management has improved, there is an agreement that monitoring and corporate governance of state-owned enterprises should be enhanced. Monetary policy will aim at containing inflation by targeting reserve money while building up official foreign exchange reserves. To mitigate risks of future debt problems, the program includes a well-defined and cautious debt strategy. The authorities are taking steps to reinvigorate their cotton sector reform efforts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet